PENGARUH IMBAL JASA DAN BEBAN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT AGAPE PRATAMA INDONESIA - Novianti, Novianti (Fakultas Ekonomi Universitas IBA, 2018)
Research is a scientific study that aims to determine the effect of service rewards and workload on employee performance of PT Agape Pratama Indonesia. The number of samples used were 26 respondents. Through the questionnaires the data were collected and analyzed using descriptive statistics and parametric inferential statistics. Descriptively the three research variables showed a good tendency. Inferentially parametric, multiple linear regression results show simultaneously significant influence of variable yield and workload to employee performance variable. However, the partial two variables did not show any significant effect on employee performance variable.